Why Is Water More Reactive Than Hydrogen in Photocatalytic CO2 Conversion at Higher Pressures? Elucidation by Means of X-Ray Absorption Fine Structure and Gas Chromatography–Mass Spectrometry - Zhang, Hongwei; Izumi, Yasuo (Frontiers in Chemistry, 2018)
Photocatalytic conversion of CO2 into mainly methane using Pd/TiO2 photocatalyst proceeded faster at 0.80 MPa using water rather than hydrogen as a reductant. It was contradictory because the former reaction (CO2 + water) is consisted of water photosplitting and the latter reaction (CO2 + hydrogen). To elucidate the reason, Pd and Ti K-edge X-ray absorption fine structure (XAFS) was monitored during CO2 photoconversion using H2 or moisture and the exchange reaction of 13CO2 at Pd/TiO2 surface was also monitored. As the result, the coordination number, N(Ti–O) and N[Ti(–O–)Ti] values decreased from original values for TiO2 crystalline (6 and 12) to 4.9–5.7 and 9.7–10.6 under CO2 and moisture in contrast to smaller decreases under CO2 and H2 and under Ar. The exchange of gas-phase 13CO2 with preadsorbed 12CO2 reached the equilibrium in 20 h with a rate constant of 0.20 h−1. The reason of higher activity using water rather than H2 could be explained owing to the oxygen vacancy (Ov) sites as confirmed by XAFS. The reaction of TiO2 surface with water formed Ov sites responsible for water oxidation, specially separated from Pd nanoparticle sites for CO2 reduction. Pd nanoparticle sites were competed by CO2 and H species and the photoconversion of CO2 was suppressed at the elevated pressure of CO2 + H2.